PENGARUH SISTEM INFORMASI MANAJEMEN (SIM) TERHADAP EFEKTIFITAS PENGAMBILAN KEPUTUSAN DI SEKRETARIAT DAERAH KOTA MANADO - TOREH, VIDIA; SONDAKH, TELLY; DENGO, SALMIN (JURNAL ADMINISTRASI PUBLIK, 2014)
ABSTRACT :Management Information System (SIM) is very important for an organizationseen in relation to the importance of information for everyone who lead units or managerialfunctions, especially in decision making. However, no SIM have not been effectively managedand utilized for decision-making at many institutions or government offices. Connection with theforegoing, this study is intended to determine the effect on the effectiveness of managementinformation system decision-making in Manado City Secretariat.The research method used a quantitative method. Source of data / research respondents were asmany as 36 employees were taken at random from the elements of leadership (assistant, headsection and subsection heads) and executive employees / staff at the Regional Secretariat of thecity of Manado. The type of data that is collected primary data collected using questionnairesand assisted with interview guide. The analysis technique used for hypothesis testing is statisticalanalysis of linear regression and product moment correlation.Statistical analysis showed: (1) Variable regression coefficient of the effectiveness ofmanagement information system decision-making is a positive and very significant meaning and(2) The correlation coefficient and the variable power of determination of the effectiveness ofmanagement information system decision-making is high / strong and significant.Based on the conclusion of research results, the effect of management information systems andcorrelates of high and significant impact on the effectiveness of decision-making in Manado CitySecretariat; means that the level of effectiveness of decision-making in Manado City Secretariatat the dominant level is influenced or determined by the management information system (SIM)is executed.Based on the conclusion of the study suggested: (1) The quality of the information submitted tothe management / leadership for making a decision must always be guaranteed (the latest /current, complete, accurate), so the decision is always right (2) The information required byleaders to decision-making purposes should be available at all times, so that at any time requiredcan be met on time.Keywords: Management Information Systems, Decision Making.